Analisa Performa Bahan Bakar Minyak Premium dan Bahan Bakar Gas CNG pada Mesin Toyota Limo - Batutah, Moh Arif ; Muhaimin , Ahmat (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
This research aims to obtain performance of premium fuel (BBM) and gas fuel or Compressed Natural Gas (CNG) on the Toyota Limo engine by adding a converter and testing using dynotest equipment to calculate torque, torque effective and fuel consumption. The test results were use of CNG fuels produces power and torque better than premium fuel, power has increased by 5.88% while torque has increased by 6.97%, minimum specific fuel consumption at 4500 rpm for premium fuel is 0.165 kg / kWh while for CNG fuel is 0.024 kg / kWh.